Training in surgery : the essential curriculum - Borley, Neil R.; Gardiner, Matthew D. (Oxford specialty training, 2009)
Training in Surgery is the first title in a new series aimed at postgraduate trainees. Using an attractive, highly illustrated double-spread layout it follows the Intercollegiate Surgical Curriculum Project and reflects the new surgical specialty training curriculum in a clear and concise style.